Controlling water deficiency as an abiotic stress factor to improve tomato nutritional and flavour quality - Ning Jin; Dan Zhang; Li Jin; Shuya Wang; Xiting Yang; Yongzhong Lei; Xin Meng; Zhiqi Xu; Jianhong Sun; Jian Lyu; Jihua Yu (Food Chemistry: X, 2023)
Water deficit (WD) irrigation techniques to improve water use efficiency have been rapidly developed. However, the effect of WD irrigation on tomato quality has not been sufficiently studied. Here, we investigated the effects of varying water irrigation levels [T1–T4: 80%, 65%, 55%, and 45% of maximum field moisture capacity (FMC)] and full irrigation (CK: 90% of maximum FMC) on tomato fruits from the mature-green to red-ripening stages, to compare the nutritional and flavour qualities of the resulting tomatoes. The proline, aspartic, malic, citric, and ascorbic acid contents increased, phenylalanine and glutamic acid contents decreased, and the total amino and organic acid contents increased by 18.91% and 26.12%, respectively, in T2-treated fruits. Furthermore, the T2-treated fruits exhibited higher K and P contents alongside improved characteristic aromas. These findings provide novel insights for further improvements in tomato quality while also developing water-saving irrigation techniques.